Comparison of sealing ability of bioceramic sealer, AH plus, and guttaflow in conservatively prepared curved root canals obturated with single-cone technique: An In vitro study - Shalan Kaul; Ajay Kumar; Bhumika Kamal Badiyani; Laxmi Sukhtankar; M Madhumitha; Amit Kumar (Wolters Kluwer Medknow Publications, 2021)
Background: Inadequate obturation techniques of the root canal system have been found to be the most frequent reason of failure post root canal treatment. An ideal endodontic sealer should fulfill all ideal requisites. The present study aimed to compare apical sealing ability between bioceramic (BC) sealer, GuttaFlow, and AH Plus. Methodology: One hundred and twenty-five curved roots of maxillary and mandibular third molar teeth with fully formed apex were collected for this study. The root canals were cleaned and shaped using a standard single-cone preparation to file at the established working length and divided into five groups of 25 each. Dye leakage was carried out. Group A: with GP, using EndoSequence BC sealer with conventional with 4% gutta-percha (Brasseler USA, Savannah, Georgia, USA); Group B: with ceramic coated with 4% gutta-percha (Brasseler USA, Savannah, Georgia, USA); Group C: with GP, using AH Plus sealer (Dentsply, De-Trey Konstanz, Germany) with 4% gutta-percha; Group D: with GuttaFlow bioseal (Roeko-Coltène/Whaledent, Langenau, Germany) with 4% Gutta-percha; and Group E is a negative control group. Statistical analysis was done using the Statistical Package for the Social Sciences software and Student's unpaired t-test. Results: The group AH Plus showed more leakage values than the GuttaFlow group and of two groups of BC sealer and negative control. Student's unpaired t-test disclosed no significant difference (P < 0.05) between the groups. Conclusion: None of the sealers used in the study could completely seal the apical foramen to have a fluid-tight seal.